A high-activity bimetallic OER cocatalyst for efficient photoelectrochemical water splitting of BiVO4. Issue 16 (7th April 2020) - Hu, Ruolin; Meng, Linxing; Zhang, Jiaxu; Wang, Xiang; Wu, Sijie; Wu, Zhou; Zhou, Rui; Li, Liang; Li, Dong-Sheng; Wu, Tao
Abstract : High-activity bimetallic oxygen evolution reaction (OER) cocatalyst for efficient photoelectrochemical water splitting of BiVO4 . Abstract : BiVO4 has been widely used as a photoanode material, while the slow surface oxygen evolution reaction (OER) kinetics still severely hinders its performance. Here, an efficient bimetallic cocatalyst (named FeSnOS) was obtained by post-annealing a Fe/Sn-containing metal chalcogenide coordination compound to enhance the OER activity of BiVO4 . The synergistic effect of Fe and Sn species in the amorphous FeSnOS cocatalyst efficiently lowers the interface impedance of the photoanode, reduces the electrochemical reaction overpotential, and promotes the surface OER dynamics. At the same time, a type-II heterojunction was constructed due to the process of post-annealing, which efficiently improves the bulk phase charge separation efficiency of the photoanode. The obtained optimal photoanode (named FeSnOS-BiVO4 ) shows a photocurrent density of 3.1 mA cm −2 at 1.23 V vs. the reversible hydrogen electrode, which is 3.4 times higher than that of the pristine BiVO4 photoanode, and its onset potential shifts negatively from 0.44 V to 0.25 V. This work presents a simple and effective method to build a bimetallic cocatalyst for improved photoelectrochemical performance, which extends the application of polymetallic metal chalcogenide complexes.